Experimental film - Files, Gemma (CZP, ChiZine Publications, 2016)
This is a contemporary ghost story in which former Canadian film history teacher Lois Cairns - jobless and depressed in the wake of her son's autism diagnosis - accidentally discovers the existence of lost early 20th century Ontario filmmaker Mrs. A. Macalla Whitcomb. By deciding to investigate how Mrs. Whitcomb's obsessions might have led to her mysterious disappearance, Lois unwittingly invites the forces which literally haunt Mrs. Whitcomb's films into her life, eventually putting her son, her husband and herself in danger.